A case report on the Siddha management of chronic diverticulosis in an elderly Indian patient - Vinubharathi Balasubramaniam (Bioinformation, 2026)
A 78-year-old male with a long-standing history of constipation-predominant diverticulitis and recurrent lower gastrointestinal bleeding presented with persistent abdominal pain, bloating, indigestion and mild rectal bleeding despite continuous conventional treatment. The condition was interpreted as chronic diverticulosis based on Siddha diagnostic principle. The patient showed progressive symptom relief with post-treatment ultrasonography revealing no acute abnormalities following sustained Siddha management. The Diverticulitis Quality of Life (DV-QOL) score improved markedly from 3.8 to 0.14 over one year, indicating significant enhancement in quality of life.